Resistome in Lake Bolonha, Brazilian Amazon: Identification of Genes Related to Resistance to Broad-Spectrum Antibiotics - Alves, Jorianne; Dias, Larissa; Mateus, Jackeline; Marques, Joana; Graças, Diego; Ramos, Rommel; Seldin, Lucy; Henriques, Isabel; Silva, Artur; Folador, Adriana (Frontiers in Microbiology, 2020)
Resistance to antibiotics is one of the most relevant public health concerns in the world. Aquatic environments play an important role because they are reservoirs for antibiotic resistance genes and antibiotic-resistant strains, contributing to the spread of resistance. The present study investigated the resistome in Lake Bolonha (three sampling sites) in the Amazon region using a metagenomics approach and culture-dependent methods. Whole-metagenome-based results showed that the most abundant phyla were Protobacteria, Actinobacteria, Firmicutes, Bacteroidetes and Cyanobacteria. The composition of the resistome demonstrated that the genes that confer resistance to β-lactams were prevalent at all sampling sites, followed by genes conferring resistance to aminoglycosides and tetracycline. Acquired genes encoding extended-spectrum β-lactamases (e.g., blaCTX-M) and resistance to carbapenems (e.g., blaIMP and blaVIM) were detected through metagenome analysis. Bacteria were isolated from culture medium supplemented with cefotaxime or imipenem, and isolates were identified and analyzed for their antibiotic susceptibility profiles and resistance genes. In total, 98 bacterial isolates belonging to the genera Pseudomonas (37), Acinetobacter (32), Klebsiella (13), Enterobacter (9), Pantoe (3), Stenotrophomonas (3), and Methylobacterium (1) were obtained. Among isolates, the most abundant genes were blaCTX-M (28.3%), blaSHV (22.6%) and blaTEM (18.8%) in isolates from cefotaxime-supplemented medium and blaVIM (28.8%) and blaIMP (22.2%) in isolates recovered from imipenem-supplemented medium. The genes intl1 and intl2 were detected in 19.3% and 7.1% of isolates. Antibiograms showed that 94.9% (from cefotaxime-supplemented medium) and 85.7% (from imipenem-supplemented medium) of the isolates were multidrug resistant. Besides cefotaxime and imipenem, isolates were mostly resistant to aztreonam (91.8%), amoxicillin (98.8%), ampicillin (82.6%), and nalidixic acid (77.5%). Hence, the present study demonstrates that lake Bolonha is a reservoir of bacteria resistant to antibiotics and resistance genes, some of which are of critical importance to human health.